USE OF PICTURE STORIES WITH THE THEME OF FEMINISM TO INCREASE GENDER AWARENESS IN LANGUAGE CLASSES - Dewi, Indah Purnama; Ambarwati, Evi Karlina; Utami, Praditya Putri (STKIP Persada Khatulistiwa Sintang, 2025)
Gender awareness is an important aspect of education that is often under-emphasized in the curriculum. Gender inequality and stereotypes still occur in various environments, including schools. Picture stories with the theme of feminism can be an effective tool in increasing gender awareness among students, especially in language classes that often use literature as a learning medium. This study aims to examine the effectiveness of using feminism-themed picture stories in increasing students' gender awareness in language classes. The study also aims to see the extent to which illustrated stories can change students' views on gender roles and gender inequality. This study uses a classroom action research method (CAR) which involves two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data was collected through observations, interviews, and questionnaires. The participants in this study are students of a language class at a high school in Indonesia. The results of the study show that the use of picture stories with the theme of feminism can significantly increase students' gender awareness. Students become more critical of gender stereotypes and better understand the importance of gender equality. In addition, illustrated stories help students to be more involved in class discussions and voice their views on gender issues. Picture stories with the theme of feminism are an effective tool to increase gender awareness in language classes. This method not only improves students' understanding of gender issues, but also encourages their active participation in class discussions. The use of this media is expected to be adopted more widely in education to reduce gender inequality and form a more gender-conscious generation.